Alcohol consumption and telomere length: observational and Mendelian randomisation approaches - Topiwala, A; Taschler, B; Ebmeier, KP; Smith, S; Zhou, H; Levey, DF; Codd, V; Samani, N; Gelernter, J; Nichols, TE; Burgess, S (2021)
Alcohols impact on telomere length, a proposed marker of biological age, is unclear. We performed the largest observational study to date and compared findings with Mendelian randomization (MR) estimates. Two-sample MR used data from a recent genome-wide association study (GWAS) of telomere length. Genetic variants were selected on the basis of associations with alcohol consumption and alcohol use disorder (AUD). Non-linear MR employed UK Biobank individual data. MR analyses suggest a causal relationship between alcohol and telomere length: both genetically predicted alcohol traits were inversely associated with telomere length. 1 S.D. higher genetically-predicted log-transformed alcoholic drinks weekly had a -0.07 S.D. effect on telomere length (95% confidence interval [CI]:-0.14 to -0.01); genetically-predicted AUD -0.06 S.D. effect (CI:-0.10 to -0.02). Results were consistent across methods and independent from smoking. Non-linear analyses indicated a potential threshold relationship between alcohol and telomere length. Our findings have implications for potential aging-related disease prevention strategies.